Modelling the tongue-of-ionisation using CTIP with SuperDARN electric potential input: verification by radiotomography - S. E. Pryse (Annales Geophysicae, 2009)
Electric potential patterns obtained by the SuperDARN radar network are used as input to the Coupled Thermosphere-Ionosphere-Plasmasphere model, in an attempt to improve the modelling of the spatial distribution of the ionospheric plasma at high latitudes. Two case studies are considered, one under conditions of stable IMF Bz negative and the other under stable IMF Bz positive. The modelled plasma distributions are compared with sets of well-established tomographic reconstructions, which have been interpreted previously in multi-instrument studies. For IMF Bz negative both the model and observations show a tongue-of-ionisation on the nightside, with good agreement between the electron density and location of the tongue. Under Bz positive, the SuperDARN input allows the model to reproduce a spatial plasma distribution akin to that observed. In this case plasma, unable to penetrate the polar cap boundary into the polar cap, is drawn by the convective flow in a tongue-of-ionisation around the periphery of the polar cap.